2013
DOI: 10.1021/jp4048083
|View full text |Cite
|
Sign up to set email alerts
|

Light Absorption in Organic Thin Films: The Importance of Oriented Molecules

Abstract: In this work we apply a joint experimental and theoretical approach to investigate thin films of side chain substituted dicyanovinyl quaterthiophenes (DCV4T-Et2) and DCV4T-Et2:C60 blends, prototypic absorbers for small molecule organic solar cells. Structural characterization of the morphology of thin films thermally deposited at different substrate temperatures on a silica surface was performed by variable angle spectroscopic ellipsometry, grazing incidence X-ray diffraction, and atomic force microscopy measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
44
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(52 citation statements)
references
References 27 publications
(38 reference statements)
6
44
0
1
Order By: Relevance
“…The features at early times resemble those of the solvated molecule (Figure 4b), suggesting the initial formation of an amorphous film with non-planar TT molecules.Agradual red shift in absorption ensues,s uch that the lowest energy band extends from 525-700 nm. [18] Changes in TT film absorption suggest ar eorganization that reduces the internal dihedral angle between the two thiophenes [19] and thereby increases electron delocalization. TT'ss lightly larger film absorptivity may result from its greater tendency for orientation relative to the substrate (see below).…”
mentioning
confidence: 99%
“…The features at early times resemble those of the solvated molecule (Figure 4b), suggesting the initial formation of an amorphous film with non-planar TT molecules.Agradual red shift in absorption ensues,s uch that the lowest energy band extends from 525-700 nm. [18] Changes in TT film absorption suggest ar eorganization that reduces the internal dihedral angle between the two thiophenes [19] and thereby increases electron delocalization. TT'ss lightly larger film absorptivity may result from its greater tendency for orientation relative to the substrate (see below).…”
mentioning
confidence: 99%
“…Instead, the dispersability is determined by the surface properties of the hybrid material. [5,6] In this regard, Kunz et al have shown that the intercalation of [Ru(bpy) 3 ] 2+ (bpy = 2,2'-bipyridine) into as ynthetic clay mineral leads to the polarized emission of light. [2] Al ayered host may offer the additional advantage of pronounced inherent structural anisotropy.Consequently,the interlayer structure formed by the intercalation of organic compounds between asandwich of two layers ensures awelldefined orientation in the confined space.…”
mentioning
confidence: 99%
“…The observed orientation is most likely a result of the spin‐coating process and π–π stacking interaction between the polythiophene backbones. The mean orientation angle α of the transition dipole moment concerning the surface normal, which was calculated from the order parameter S ( k in‐plane , k out‐of‐plane ), is 63 ± 1° in the undoped state and slightly increases to 66 ± 1° for the doped film. While for small planar organic molecules, the orientation of the transition dipole moment is within the molecular plane and the orientation of molecule and transition dipole are the same, the alignment of polymer chains cannot be deduced based on α in general.…”
Section: Resultsmentioning
confidence: 99%